Artificial Intelligence (AI) and its applicability in Banking and Financial system in India - Murugan, M.Sakthivel; Sujatha, T. (International Journal of Psychosocial Rehabilitation, 2020)
The Advent of Computer and Information Technology Scientists have innovated human intelligence with the help of machine (computer) and invented artificial intelligence with enables Computer machine to think, learn, act like human beings. the Artificial intelligence technology which does every work on machine learning, deep learning, cloud computing and black chain technology is an extension to Information science and computer technology and is being used and adopted in various officers, industries, institutions and banking is which an essence to help the banking system and customer support and satisfaction. An attempt is focused in this paper to highlight the use of artificial intelligence usage in the banking and financial system. This paper elaborates the areas of usage of banking and financial institution utilizes artificial intelligence system and also highlights the significance and benefits of usage of banking and financial system in India. This paper also overviews of case study pertaining to usage of Artificial Intelligence in banking sector.